RANCANG BANGUN ALAT PENGASAPAN IKAN DENGAN BAHAN BAKAR LIMBAH KAYU SEBAGAI PEMANFAATAN LIMBAH PENGRAJIN KAYU DI JEPARA (Jurnal Inovasi Mesin, 2022)
The purpose of this research is to know the design and working drawings of the fish smoking tool. To know the design stages of the fish smoking tool. To know the budget required in making fish smoking equipment. A fish smoker is a tool that functions to dry fish with the heat contained in the smoke. Fish smoking is an agricultural product processing technique that aims to preserve fish and increase the selling price of fish in the market. In addition to increasing the selling price, smoking fish also serves to improve the taste of fish. By making this design it can be concluded that this tool can utilize wood waste as a heating medium in fish smokers. The budget required for making this tool is Rp. 4,601,000.00 with the tool specifications listed in the attachment.